1978
DOI: 10.1002/jgt.3190020207
|View full text |Cite
|
Sign up to set email alerts
|

On the eulericity of a graph

Abstract: The eulericity E ( G ) of a bridgeless 'graph G is defined as the least number of eulerian subgraphs of G which together cover the lines of G.A 1-1 correspondence is shown to exist between the k-tuples of eulerian subgraphs of G and the proper flows (mod2k) on a given network based on G. The inequality r ( G ) 1 3 then follows from a result of Jaeger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…We excluded studies that did not report both isotopes or did not include soil water. Stable isotope data reported in the original papers were extracted either directly from tables or the text or through the data extraction tool Graph Data Extractor (Matthews, ) or obtained from digital repositories. The database includes isotope data from soil water ( n = 5,328) and xylem water ( n = 2,579) from 77 study sites (some papers reported data from more than one site, so the number of study sites is larger than the numbers of screened papers) belonging to four different climate zones of the world, according to Köppen classification (Peel, Finlayson, & McMahon, ; Figure ; Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…We excluded studies that did not report both isotopes or did not include soil water. Stable isotope data reported in the original papers were extracted either directly from tables or the text or through the data extraction tool Graph Data Extractor (Matthews, ) or obtained from digital repositories. The database includes isotope data from soil water ( n = 5,328) and xylem water ( n = 2,579) from 77 study sites (some papers reported data from more than one site, so the number of study sites is larger than the numbers of screened papers) belonging to four different climate zones of the world, according to Köppen classification (Peel, Finlayson, & McMahon, ; Figure ; Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Such decompositions represent a counterpart to decompositions into even subgraphs, which were mainly used while proving various flow problems (see e.g. [6,9]). Historically speaking, as a topic in graph theory, decomposing into subgraphs of a particular kind started with the paper of Erdös et al [2].…”
Section: Odd Edge-colorings and Odd Chromatic Indexmentioning
confidence: 99%
“…Tutte [19,20] and Matthews [17] conjectured that if a 2-edge-connected graph G has no subgraph contractible to the Petersen graph, then G has a 3-colorable double cycle cover (i.e., a collection of three even subgraphs such that each edge of G lies in exactly two of them). We showed before (see [5 or 6]) that any supereulerian graph has a 3-colorable double cycle cover.…”
Section: O(g)=[odd-degree Vertices Of G]mentioning
confidence: 99%